Alkoxy chain regulated stimuli-responsive AIE luminogens based on tetraphenylethylene substituted phenanthroimidazoles and non-doped OLEDs with negligible efficiency roll-off. Issue 12 (26th February 2020) - Qiu, Zhipeng; Yang, Zhiwen; Chen, Wen-Cheng; Xing, Longjiang; Hu, Sheng; Ji, Shaomin; Yang, Qingdan; Cai, Ning; Ouyang, Xinhua; Huo, Yanping
Abstract : Three novel tetraphenylethylene derivatives with different lengths of alkoxy chains, named TPEO1-PPI, TPEO4-PPI and TPEO6-PPI, are synthesized and fully characterized. Abstract : Three novel tetraphenylethylene derivatives with different lengths of alkoxy chains, named TPEO1-PPI, TPEO4-PPI and TPEO6-PPI, are synthesized and fully characterized. All of them show obvious aggregation-induced emission (AIE) properties with high photoluminescence quantum yield (PLQY) in the film state. The synthesized emitters exhibit green or blue emission in the solid state, a significant blue-shift is observed in emission spectra upon increasing the length of alkoxy chains. Interestingly, all these compounds demonstrate mechanofluorochromic (MFC) properties with a significant red-shift after mechanical grinding. X-ray diffraction results indicate that the MFC properties can be attributed to the morphological transition from crystalline to amorphous. Due to the high PLQY in film states and matched energy levels, the device based on TPEO4-PPI shows an outstanding maximum luminance (up to 15 995 cd m −2 at 8.7 V), remarkable electroluminescence (EL) efficiencies (4.51 lm W −1 and 4.22 cd A −1 ) and a maximum external quantum efficiency (EQE, 4.07%). In addition, these devices show small efficiency roll-off, the corresponding EQE remained at 3.59% at a high luminance of 1000 cd m −2 . These results indicate that the length of the peripheral alkoxy chains connected to the terminal group can have a great influence on the photophysical properties, which deserves attention in molecular design.